Computer physicochemical modeling of hydrogen and methane behavior in aqueous solutions - Slovotenko, Nadiya; Bornyak, Ulyana (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. Increasing interest of the scientific community to the natural hydrogen growths due its potential role as a substitute for traditional hydrocarbon energy sources. The initial migration of hydrogen occurs in the aqueous solution. Hydrogen transportation with subsequent accumulation is possible only in the underground aquifers. The heterogenization of the aqueous solution is determined by both P-T conditions and its saturation with gases and background salt composition. In our opinion, the model of the functioning of the hydrogen system deserves careful attention and is extremely relevant. The problem facing us is the interaction of hydrogen flows with existing deposits of predominantly methane composition. Understanding the mechanisms and dynamics of these processes requires the analysis of a complex multi-phase physicochemical system, which can be implemented by the computer physicochemical modeling of the hydrogen and methane behavior in modern software packages.The purpose of the study: to determine behavior features of the hydrogen and methane in the natural solutions of different salinities, namely, to establish the saturation points of hydrogen and methane solutions at different temperatures and pressures using numerical physicochemical modeling.Research methodology. GEM-Selektor (GEMS) is a software package created by a group led by D. Kulik, the software package is distributed by the Paul Scherrer Institute. The computational algorithms are based on the principle of Gibbs energy minimization (GEM), and allow interactive thermodynamic modeling of heterogeneous aqueous geochemical systems. Includes a built-in thermodynamic database in both thermochemical and reaction formats. To model the studied system, we used the MINES thermodynamic database, which was created and maintained by Professor Alexander Gysi from the Bureau of Geology and Mineral Resources, New Mexico, USA.Results. The modeled system was a solution (of different salinities: 0 and 10 wt. % NaCl eq.), equilibrated with a sandstone of the specified composition. It was duplicated at different temperatures from 10 °C to 240 °C and a pressure of 1751 bar with a step of 10 °C and 50 bar. The simulation conditions included: a temperature interval from 10 to 240 °C, and pressure parameters from 1 to 1751 bar. The results of the study include the gas saturation of electrolyte solutions of variable salinity (0 and 10 wt. % NaCl equiv.), which are demonstrated using mole fraction diagrams multiplied by 100%, depending on temperature and pressure. The saturation results of the different salinities solutions with hydrogen and methane are compared for a model with hydrostatic pressure and a geothermal gradient of 25 °C/km.Conclusions. The solubility of hydrogen and methane in aqueous sodium chloride solutions varies with temperature and pressure and increases with increasing temperature and pressure. During the dissolution of gases, pressure plays a greater role than temperature. A mixture of hydrogen and methane equilibrated with the formation solution will contain more hydrogen than methane at pressures above 200 bar, and more methane than hydrogen at pressures below 200 bar. At great depths and under high pressure hydrogen dissolves better in aqueous solutions than methane, and in near-surface conditions hydrogen dissolution is reduced.